3D-perfusion analysis of burn wounds using hyperspectral imaging. Issue 1 (February 2021) - Marotz, Jörg; Schulz, Torsten; Seider, Sebastian; Cruz, Diogo; Aljowder, Ahmed; Promny, Dominik; Daeschlein, Georg; Wild, Thomas; Siemers, Frank
Highlights: Hyperspectral imaging parameter provide a detailed insight into the perfusion of burn wounds. A new model-based data processing method determines 26 parameters describing the layered structure of perfused skin including 12 perfusion parameters. Analysis of the wound perfusion over the first 72 h after burn enables an early classification. Abstract: Background: Determination of the depth of burn wounds is still a challenge in clinical practise and fundamental for an optimal treatment. Hyperspectral imaging (HSI) has a high potential to be established as a new contact-free measuring method in medicine. From hyperspectral spectra 3D-perfusion parameters can be estimated and the microcirculatory of burn wounds over the first 72 h after thermal injury can be objectively described. Methods: We used a hyperspectral imaging camera and extended data processing methods to calculate 3D-perfusion parameters of burn wounds from adult patients. The data processing results in the estimation of perfusion parameters like volume fraction and oxygenation of haemoglobin for 6 different layers of the injured skin. The parameters are presented as depth profiles. We analyzed and compared measurements of wounds of different degrees of damage and present the methodology and preliminary results. Results: The depth profiles of the perfusion parameters show characteristic features and differences depending on the degree of damage. With Hyperspectral Imaging and the advanced data processing the perfusion characteristics of burn wounds can be visualized in more detail. Based on the analysis of this perfusion characteristics, a new and better reliable classification of burn degrees can be developed supporting the surgeon in the early selection of the optimal treatment.